Optimalisasi Kesehatan Lansia Melalui Pemberdayaan Masyarakat: Pemeriksaan Kesehatan Dan Edukasi Gaya Hidup Lansia Upaya Pencegahan Penyakit Degeneratif - Thristy, Isra; Hutagaol, Nadya Utami; Zahara, Rita; Koto, Ulfa; Br. Sembiring, Tiara Amanda; Damanik, Syifa Akbar; Sari, Ria Wilan Permata; Putri, Humairani; Putri, Maduri Yaner; Noval, Wildana Luthfi; Dorando, Raja Mahendra Putra (Peneliti.net, 2025)
Geriatric syndrome is a collection of health conditions often experienced by the elderly, including cognitive problems, mobility, and impaired daily functioning that negatively influence the routine tasks and standard of living of the seniors. To identify risk factors that influence cognitive decline in the elderly and geriatric syndrome. In the implementation of community service activities in Kutalimbaru Village Hamlet III using health education methods that prioritize active community involvement in each program as well as health checks and elderly lifestyle education. This community service activity in Dusun III Kutalimbaru Village was attended by 27 people. There were 9 people with hypertension, 5 people with high cholesterol, 15 people with hyperuricemia, 7 people with obesity, 2 people with high blood sugar. From the results of the health checks that have been carried out, several abnormal data are found, so counseling on healthy lifestyles and routine health checks is needed for the community in Kutalimbaru village hamlet III.